2018
DOI: 10.3389/fpsyt.2018.00416
|View full text |Cite
|
Sign up to set email alerts
|

Five Interpersonal Factors Are Predictive of the Response to Treatment of Major Depression With Antidepressants in Primary Care

Abstract: Introduction: Factors relating to the interpersonal relationship between the patient and their physician and social environment are important components, which contribute to their response to treatment for major depressive disorder. This study aimed to assess the influence of optimism, perfectionism, therapeutic alliance, empathy, social support, and adherence to medication regimen in the response to antidepressant treatments in the context of normal primary care clinical practice.Method: We conducted a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…The relationship between the professional and the user has been described as one of the main elements for treatment adherence, as long as it takes place in a collaborative environment, far from coercion, in which the needs of the person are considered (Salazar‐Fraile et al . ). To create this therapeutic alliance, the fear or the desire to avoid, typical stigmatizing attitudes, should not be present.…”
Section: Relevance For Clinical Practicementioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between the professional and the user has been described as one of the main elements for treatment adherence, as long as it takes place in a collaborative environment, far from coercion, in which the needs of the person are considered (Salazar‐Fraile et al . ). To create this therapeutic alliance, the fear or the desire to avoid, typical stigmatizing attitudes, should not be present.…”
Section: Relevance For Clinical Practicementioning
confidence: 97%
“…Through the intervention based on direct contact described, carried out during their training, we believe that future nurses could enter professional practice with a lower burden of stigmatizing attitudes, thus facilitating the creation of therapeutic alliance, one of the most important tools for successful outcomes (Martin et al 2000). The relationship between the professional and the user has been described as one of the main elements for treatment adherence, as long as it takes place in a collaborative environment, far from coercion, in which the needs of the person are considered (Salazar-Fraile et al 2018). To create this therapeutic alliance, the fear or the desire to avoid, typical stigmatizing attitudes, should not be present.…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…A good therapeutic alliance can improve the symptoms and functioning of people with mental disorders (Kreyenbuhl et al., 2009; Priebe et al., 2011; Salazar‐Fraile et al., 2018; Shattock et al., 2017). Some studies have suggested that the therapeutic alliance is an essential element for increasing the effectiveness of pharmacological or psychological treatments (Horvath et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are several mechanisms that may have mediated this association. First, there is some evidence to suggest that hierarchical cultures with a high power distance may be associated with greater peer support [ 33 ] and a clearer sense of “belonging” [ 34 ]; these factors have been associated with a better response to antidepressants in earlier analyses [ 14 , 16 ]. Second, in such cultures in individuals in a position of “less power” (in this case, patients participating in a trial of antidepressants) have higher levels of trust in those considered to have “more power” (in this case, doctors or researchers) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%